The theories of state origins as an analytical tool for the research of the state institutional system - Кліпкова, Г. О. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2016)
The article discusses the genesis of the state institutions using the theories of the state origins. The analysis of the informal institutions origin in the modern states with the tools of the early state theory is given. Military-fiscal theory and the concept of the violent entrepreneurs, in our view, make a significant contribution to the study of non-Western state and institutional systems.